Systematic review on spheroids from adipose‐derived stem cells: Spontaneous or artefact state?. Issue 12 (9th October 2022) - Di Stefano, Anna Barbara; Urrata, Valentina; Trapani, Marco; Moschella, Francesco; Cordova, Adriana; Toia, Francesca
Abstract: Three‐dimensional (3D) cell cultures represent the spontaneous state of stem cells with specific gene and protein molecular expression that are more alike the in vivo condition. In vitro two‐dimensional (2D) cell adhesion cultures are still commonly employed for various cellular studies such as movement, proliferation and differentiation phenomena; this procedure is standardized and amply used in laboratories, however their representing the original tissue has recently been subject to questioning. Cell cultures in 2D require a support/substrate (flasks, multiwells, etc.) and use of fetal bovine serum as an adjuvant that stimulates adhesion that most likely leads to cellular aging. A 3D environment stimulates cells to grow in suspended aggregates that are defined as "spheroids." In particular, adipose stem cells (ASCs) are traditionally observed in adhesion conditions, but a recent and vast literature offers many strategies that obtain 3D cell spheroids. These cells seem to possess a greater ability in maintaining their stemness and differentiate towards all mesenchymal lineages, as demonstrated in in vitro and in vivo studies compared to adhesion cultures. To date, standardized procedures that form ASC spheroids have not yet been established. This systematic review carries out an in‐depth analysis of the 76 articles produced over the past 10 years and discusses the similarities and differences in materials, techniques, and purposes to standardize the methods aimed at obtaining ASC spheroids as already described for 2D cultures. Abstract : Our proposed model of spheroid isolation from liposuction fat. The tissue disintegration releases the pre‐existing spheroids as intact structures. This could be the ideal technique to culture cells in suspension because it avoids a preliminary adhesion isolation step and thus an upstream cell selection. In addition, spheroids can be differentiated.